Hepatoprotective Effect of Lactobacillus plantarum HFY09 on Ethanol-Induced Liver Injury in Mice - Gan, Yi; Tong, Jin; Zhou, Xianrong; Long, Xingyao; Pan, Yanni; Liu, Weiwei; Zhao, Xin (Frontiers in Nutrition, 2021)
Lactobacillus plantarum is a bacterial strain that is used as a probiotic with health-promoting effects. Our study investigated the hepatoprotective effect of Lactobacillus plantarum HFY09 (LP-HFY09) in mice with ethanol-induced liver injury. The protection afforded by LP-HFY09 was evaluated by observing the morphology of hepatic tissue and measuring liver lipid indexes and function indexes, levels of anti-oxidative enzymes and anti-inebriation enzymes, as well as oxidative metabolism-related gene expression. Gavage administration of LP-HFY09 (1×109 CFU/kg body weight) limited the loss of body weight, alcohol damage to the liver, and maintained the normal hepatic tissue morphology. LP-HFY09 intervention in ethanol-induced mice led to decreases in serum triglyceride, total cholesterol, aspartic transaminase, alanine transaminase, hyaluronidase and precollagen III, and increases in liver alcohol dehydrogenase and acetaldehyde dehydrogenase. LP-HFY09 assisted with alleviating inflammation by elevating the level of interleukin 10 (IL-10) and decreasing the levels of pro-inflammatory factors (IL-6, IL-1β, and tumor necrosis factor-α). LP-HFY09 significantly elevated hepatic levels of superoxide dismutase (SOD) and glutathione, and decreased liver malondialdehyde from 3.45 to 1.64 nmol/mg protein. LP-HFY09 exhibited an overall strong regulatory effect on liver protection when compared to that of commercial Lactobacillus delbrueckii subsp. Bulgaricus. The hepatoprotective effect of LP-HFY09 was reflected by the upregulated expression of peroxisome proliferator activated-receptors α, SOD1, SOD2, glutathione peroxidase, nicotinamide adenine dinucleotide phosphate, and catalase, and the downregulated expression of cyclooxygenase-1, c-Jun N-terminal kinase, and extracellular regulated protein kinases. Administration of LP-HFY09 at a concentration of 1.0 × 109 CFU/kg body weight could be a potential intervention for people who frequently consume alcohol.